Global Warming: The Balance of Evidence and Its Policy Implications - Charles Keller (The Scientific World Journal)
Global warming and attendant climate change have been controversial for at least a decade. This is largely because of its societal implications. With the recent publication of the Third Assessment Report of the United Nations’ Intergovernmental Panel on Climate Change there has been renewed interest and controversy about how certain the scientific community is of its conclusions: that humans are influencing the climate and that global temperatures will continue to rise rapidly in this century. This review attempts to update what is known and in particular what advances have been made in the past 5 years or so. It does not attempt to be comprehensive. Rather it focuses on the most controversial issues, which are actually few in number. They are: 1-Is the surface temperature record accurate or is it biased by heat from cities, etc.? 2-Is that record significantly different from past warmings such as the Medieval Warming Period? 3-Is not the sun’s increasing activity the cause of most of the warming? 4-Can we model climate and predict its future, or is it just too complex and chaotic? 5-Are there any other changes in climate other than warming, and can they be attributed to the warming?Despite continued uncertainties, the review finds affirmative answers to these questions. Of particular interest are advances that seem to explain why satellites do not see as much warming as surface instruments, how we are getting a good idea of recent paleoclimates, and why the 20th century temperature record was so complex. It makes the point that in each area new information could come to light that would change our thinking on the quantitative magnitude and timing of anthropogenic warming, but it is unlikely to alter the basic conclusions.Finally, there is a very brief discussion of the societal policy response to the scientific message, and the author comments on his 2-year email discussions with many of the world’s most outspoken critics of the anthropogenic warming hypothesis.